Upstream activation sites of the CYC1 gene of Saccharomyces cerevisiae are active when inverted but not when placed downstream of the "TATA box". - Guarente, L (1984)
The ability of the upstream activation sites (UASs) of the yeast CYC1 gene to function when inverted or when positioned downstream of the "TATA box" is investigated. Inversion of a 130-base-pair DNA fragment bearing the UASs leaves the activity of the sites almost completely intact. In contrast, positioning the sites downstream of the TATA box or in the intron of a CYC1-ribosomal protein 51-lacZ tribrid gene almost totally abolishes their activity. In the latter construct, the separation between the UASs and TATA box is roughly equivalent to that between the elements in the intact CYC1 promoter region. The UASs are shown not to interrupt transcription of splicing in this construct since a GAL10 UAS positioned upstream of the TATA box gives rise to galactose-inducible expression of the tribrid gene. The inability of the UASs to function in the intron is partly due to sequences between the intron and the TATA box that block the activation signal. However, a large component of the inactivity of the sites in the intron appears to be their downstream location. This result is discussed in light of possible mechanisms of upstream activation in yeast.